As empresas militares privadas e o processo de pacificação no Darfur - Ramos, Lucas de Oliveira (2020)
The aim in this dissertation is to analyze the participation of Private Military Companies in military interventions. Specifically, it will try to stablish the connection, through the analysis of the role of Private Military Companies in Darfur’s conflict, what is the relation between the United States’ project of pacification in Darfur and the PMC, understanding the latter as its conducting vein. We pursue the hypothesis that, given the neoliberal modus operandi that conducts the structure of international order, which finds itself in constant process of expan-sion, the Private Military Companies would be one of the agents who would not only introject the organization model of Western political and social life to contexts beyond it, but would be the guarantors of the (re)structuration of market and, consequently, of contemporary mecha-nisms of capital accumulation. Methodologically, it is a conceptual application in a case study. In terms of techniques and research, this dissertation will use bibliographic review and document analysis. Specifically, it will revisit the literature on Private Military Companies, the conceptual arrangement on pacification by Mark Neocleous — author who outlined the concept of pacification that will be mobilized here — and from the conflict in Darfur, in addi-tion to analyzing the contracts signed by the United States with Private Military Companies and the reports produced by the latter on their activities. It is organized in three chapters, the first being an important systematization of the literature about private military companies, the second dealing with the concept of pacification and the third chapter dealing with the conflict and the Private Military Companies that operated there